Psychosocial factors affecting dietary habits of university students: A cross-sectional study. Issue 6 (June 2022) - Cheikh Ismail, Leila; Osaili, Tareq M.; Mohamad, Maysm N.; Hashim, Mona; Stojanovska, Lily; Al Daour, Rameez; Nader, Dalal; Alrayis, Hanoof; Alzaabi, Nouf Sultan; Elbarag, Lojain; Binkhadim, Shaikha; Jarrar, Amjad H.; et al.
Abstract: Background: University student transition from living at home to more independent living which might influence their eating habits. This study aims to assess the effect of psychosocial factors on eating habits among university students. Methods: A cross-sectional study was conducted among 529 students at the University of Sharjah. Participants completed a self-administered questionnaire on dietary habits, social, and psychological factors. The height and weight were also measured. Results: More than one-third of participants were classified as overweight or obese (37.6%) and 39.1% reported not engaging in regular physical activity. Less than half of the participants consumed breakfast daily (45.4%) and 83.2% consumed less than two liters of water per day. Only 28.7% and 34.0% of participants consumed fruits and vegetables daily, respectively. Almost 80% of participants reported eating when they were bored, 83.7% ate when feeling happy, and 56.5% ate when they were sad. Eating habits score was significantly lower among unmarried participants (p = 0.03), those not living with their family (p < 0.001), smokers (p = 0.001), those not engaging in regular physical activity (p < 0.001), and those who reported eating uncontrollably (p = 0.007). Conclusions: Psychosocial factors were important indicators of dietary habits among students. Implementing nutrition education campaigns and health-related courses at the university are recommended. Abstract : Body mass index; Eating habits; University students; Psychosocial factors.